Tinjauan Rechterlijk Pardon: Upaya Variasi Yurisprudensi dan Potensi Subjektivitas Hakim - Rakananda, Muhammad Rafi (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Judge's pardon (rechterlijk pardon) is a type of decision that has recently been regulated in the National Criminal Code. The birth of judge forgiveness is expected to be a new moral justice for the community. The reason is that criminal decisions in Indonesia are limited to 3 types, namely conviction, release and acquittal. This research uses a normative juridical method with a conceptual approach, legislative approach and comparative law, where this article will discuss the concept of rechterlijk pardon in Indonesia and the Netherlands and Greece. As for this research, it is found that there are similarities between Indonesian rechterlijk pardon and Greece and Indonesia and the Netherlands, where the requirements that affect the decision of rechterlijk pardon to a defendant between the Indonesian Criminal Code and the Dutch WvS are fairly similar, while the similarity with the Greek Criminal Code is the meaning of the authority of the judge to impose a pardon decision on the defendant. This can also make the same case have different decisions.